(untitled) (Acta Scientiarum. Biological Sciences, 2015)
The caatinga scrublands are relatively poorly-studied, and few data are available on the biome’s chiropteran fauna. The present study focuses on the bat community of the arboreal caatinga of Serra da Guia. Bats were trapped in mist-nets on three new moon nights per month between October, 2008, and September, 2009. A total of 157 individuals were captured, representing 12 species. Species richness estimated by Jackknife1 was 14.8. Glossophaga soricina and Carollia perspicillata were by far the most common species, accounting for 56.7% of the specimens captured. Species diversity was 1.80, while equitability was 0.72. There was no significant seasonal difference in species diversity or evenness. However, the present study recorded a clear seasonal shift in community structure. The principal difference in species composition was related to the temporal distribution of the rarest forms – all of the seven rarest species were recorded exclusively in only one season (dry or wet). The nectarivorous bats predominated numerically both in the dry season as in rainy, while frugivores became prominent, in terms of both the number of species and individuals, during the wet season. The predominance of stenodermatine bats during the wet season almost certainly reflects the increased availability of resources for this group during this part of the year.